Journal of Imagery Research in Sport and Physical Activity (De Gruyter, 2006)
Objective The Journal of Imagery Research in Sport and Physical Activity is the first peer-reviewed journal devoted to research on the role of imagery in sport, physical activity, exercise, and rehabilitation settings. Imagery, also referred to as cognitive enactment or visualization, is one of the most popular performance enhancement and rehabilitation techniques in sports and physical activity. Journal editor Sandra Moritz (University of North Dakota) is a recognized leader in the field, and the journal's editorial board represents leading institutions in the U.S., U.K., and Canada. The single destination for all imagery-related research in sports and in physical activity, the Journal of Imagery Research in Sport and Physical Activity is an indispensable tool for scholars and practitioners of imagery, sports science, kinesiology, physical education, and psychology. Topics The role of imagery in sport Physical activity Exercise Rehabilitation settings Sports science Kinesiology Physical education Psychology Article formatsOriginal research articles, reviews Information on Submission Process